Overview of Accountable Care Organizations for Oncology Specialists - Mehta, Anish J. (American Society of Clinical Oncology, 2013)
Accountable care organizations (ACOs) are poised to become major components of health care delivery in the United States. The practice of oncology, often laden with high charges, is likely to undergo major shifts as ACOs become widespread. In this article, we review the economic factors leading to the growth of ACOs and discuss some elements of the current ACO model proposed in the Affordable Care Act. Oncology specialists—in medicine, surgery, and radiation oncology—will have important roles in determining the place of specialty care in an ACO framework and will have to take the lead in educating patients, primary care physicians, and administrators on the value propositions related to their activities. We also describe how oncology specialists may participate in the model to ensure success for physicians and patients.